Can We Measure Resilience? A Proposed Method and Evidence from Countries in the Sahel - Alfani, Federica; Dabalen, Andrew; Fisker, Peter; Molini, Vasco (World Bank Group, Washington, DC, 2015)
Although resilience has become a popular concept in studies of poverty and vulnerability, it has been difficult to obtain a credible measure of resilience. This difficulty is because the data required to measure resilience, which involves observing household outcomes over time after every exposure to a shock, are usually unavailable in many contexts. This paper proposes a new method for measuring household resilience using readily available cross section data. Intuitively, a household is considered resilient if there is very little difference between the pre- and post-shock welfare. By obtaining counterfactual welfare for households before and after a shock, households are classified as chronically poor, non-resilient, and resilient. This method is applied to four countries in the Sahel. It is found that Niger, Burkina Faso, and Northern Nigeria have high percentages of chronically poor: respectively, 48, 34, and 27 percent. In Senegal, only 4 percent of the population is chronically poor. The middle group, the non-resilient, accounts for about 70 percent of the households in Senegal, while in the other countries it ranges between 34 and 38 percent. Resilient households account for about 33 percent in all countries except Niger, where the share is around 18 percent.